Exploring the concurrent validity of a linguistically responsive pre-reading assessment in bilingual children: the Urdu Phonological Tele-Assessment (U-PASS) tool - Bhalloo, Insiya; Molnar, Monika (Frontiers in Education, 2025)
IntroductionChildhood language and reading contribute to academic and socio-economic success. It is therefore important to identify school-aged children’s language and reading abilities as early as possible to provide additional support. Oral-language assessment tools are used by speech-language pathologists (SLPs) and educators for early identification of children at risk for reading difficulties. Particularly, phonological processing is an oral-language and pre-reading skill commonly used to examine reading skills at the early grade levels. However, there is a clear English-language assessment bias when it comes to these pre-reading assessment tools, which impacts clinical and research practices. Bilingual children are commonly misidentified with reading disorders–partially due to the lack of appropriate assessment tools. To address this bias, we developed and evaluated an age- and linguistically-appropriate Urdu Phonological Tele-Assessment (U-PASS) tool across three phases. The U-PASS consists of 10 phonological awareness, phonological memory, and rapid automatized naming subtests.MethodsWe tested 115 typically-developing Urdu-English simultaneous bilinguals in Grades 1–2 across Canada and Pakistan on the U-PASS, vocabulary and reading accuracy measures, and background questionnaires.ResultsItem-level analysis, involving point-biserial correlations, accuracy rates, and Cronbach’s alpha, and linear regression, involving subtest- and composite-level analysis, were used to collect evidence for U-PASS’s internal reliability and criterion-based concurrent validity.DiscussionOur linear regression analyses indicated significant phonological processing-reading associations after accounting for background variables, thereby demonstrating U-PASS’s concurrent validity for assessing Urdu word/non-word reading. The open-access tool enables SLPs and educators to provide early pre-reading assessment and support for the successful development of oral-language and reading skills in bilingual children speaking Urdu—a common, yet under-investigated, language globally.